The prevalence and profile of disabilities affecting daily activities among the elderly population in Bengaluru city, India - R., Anil; Prasad, K. N.; Puttaswamy, M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Age related changes and non-communicable diseases are the main causes of disabilities and few such disabilities require assistance for everyday tasks. The objective of the study was to estimate the prevalence of disabilities affecting daily activities and its profile among the elderly aged population in urban area. Methods:A community based, quantitative and cross sectional study was conducted among the 370 elderly subjects residing in ward 32 of Bengaluru city, India during July and August 2015. Data was collected about disabilities in basic and instrumental activities using a pretested questionnaire at their doorsteps. Scoring method was applied to assess the severity of disabilities and analysis was done. Results: The total prevalence of disabilities affecting daily activity as unable to do and with much difficulty was 13% and 9% respectively and it was more among the females. Major difficulty was in climbing the stairs (steps). Non communicable diseases lead to increase in the prevalence of basic daily activity disabilities; it was 39% in males and 50% in females. Basic activity disability between healthy and diseased elderly people was statistically significant in both males and females (p <0.05). The difference between the basic activities and instrumental activities in both males and females is statistically significant (p <0.05). Conclusions:The overall prevalence of disability of daily activities was 21%. Basic daily activities like climbing stairs, using toilet and instrumental daily activities like cooking food, and washing clothes had a higher prevalence of disabilities. Non communicable diseases increased the prevalence of disabilities.